2015
DOI: 10.1016/j.celrep.2014.12.047
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of NF-κB-Mediated Proviral and Antiviral Host Gene Expression by Primate Lentiviral Nef and Vpu Proteins

Abstract: SUMMARYNF-κB is essential for effective transcription of primate lentiviral genomes and also activates antiviral host genes. Here, we show that the early protein Nef of most primate lentiviruses enhances NF-κB activation. In contrast, the late protein Vpu of HIV-1 and its simian precursors inhibits activation of NF-κB, even in the presence of Nef. Although this effect of Vpu did not correlate with its ability to interact with β-TrCP, it involved the stabilization of IκB and reduced nuclear translocation of p65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
182
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(196 citation statements)
references
References 54 publications
11
182
0
Order By: Relevance
“…The effect of Vpr on the NF-B pathway remains controversial as well. It has been proposed that Vpr may impair NF-B nuclear translocation by inducing and/or stabilizing the IB␣ inhibitory subunit (14,74,109). In contrast, it has been suggested that Vpr interaction with TAK1 leads to IKK␣/␤ phosphorylation and ultimately results in IB␣ degradation (70,71).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of Vpr on the NF-B pathway remains controversial as well. It has been proposed that Vpr may impair NF-B nuclear translocation by inducing and/or stabilizing the IB␣ inhibitory subunit (14,74,109). In contrast, it has been suggested that Vpr interaction with TAK1 leads to IKK␣/␤ phosphorylation and ultimately results in IB␣ degradation (70,71).…”
Section: Discussionmentioning
confidence: 99%
“…Vpu, by degrading tetherin, avoids the stimulation of the NF-B pathway by tethered virions (11)(12)(13)(14). In contrast, Nef enhances NF-B activation (14) and HIV-2 Vpx, by degrading SAMHD1 (15,16), promotes infection and subsequent innate sensing in myeloid cells (17)(18)(19). The role of HIV-1 Vpr in the modulation of innate responses remains partly characterized.…”
mentioning
confidence: 99%
“…9D). These findings suggest that primate lentiviruses can, at least to some extent, uncouple the transcriptional activity of the viral LTR promoter from the state of cellular activation, possibly because Nef may support NF-B induction independently of TCR-CD3 signaling (39). However, although similar levels of HIV-1-infected (eGFP ϩ ) cells and only modest differences in eGFP expression levels were detected in RA ϩ RO ϩ Tdp and RA Ϫ RO ϩ Tm cells, only the former produced high levels of infectious HIV-1 (Fig.…”
Section: Cd4mentioning
confidence: 98%
“…These results suggest that HIV NL4.3 Vpu downmodulates NF-B downstream IKK␤. Previous studies reported that Vpu could stabilize the nuclear factor of kappa light polypeptide gene enhancer in B cells inhibitor alpha (IB␣), thus inhibiting NF-B activation (12,54). Since TNF-␣ stimulation induces IB␣ rapid degradation (55), we next compared the levels of IB␣ in response to TNF-␣ in 293T expressing Vpu or GFP.…”
Section: Nl43 Vpu Inhibits Nf-b But Not Irf3 Signaling Since the Ifmentioning
confidence: 99%